Alpha-1-antitrypsin deficiency and liver disease. - Millward-Sadler, G. H. (1981)
In this review article only the liver disease associated with aipha-1-antitrypsin deficiency will be considered. For the well recognised association with lung disease the review by Mittman is recommended.